Comparison of Heuristic Evaluation and Think Aloud Methods: A Study in Radiotherapy Contouring Software. Issue 1 (June 2014) - Ramkumar, Anjana; Song, Yu; Varga, Edit; Niessen, Wiro J.; Laprie, Anne; Rowland, Ben; Freudenthal, Adinda
During the radiotherapy planning process patient's medical images are used to determine the optimum configuration of radiation beams for their cancer treatment. The primary aim of radiotherapy planning is to maximize radiation dose to the patient's tumour while sparing their normal tissues. To achieve this, the boundary of the tumour needs to be accurately identified in the treatment planning process, especially in the step of target volume delineation. Clinically, tumour delineation is performed by physicians, either manually or using semi-automatic/automatic software based on the patient's CT, PET and/or MRI images. In addition to the expertise of the physician and choices of segmentation algorithms, the usability of the software also plays an important role in the tumour delineation process. In this paper, the usability of the IPLAN ® contouring software was evaluated. First, two evaluators assessed the software according to the heuristic evaluation method. Then three physicians evaluated the same system using the think aloud method. The outcomes of the experiments revealed different insights of the system. With the think aloud method, it was easier to identify end users' preferences regarding both software interface and hardware input tools. On the other hand, the heuristic evaluation method uncovered more specific issues with the interface. Besides, this method was able to explore more details regarding individual functionalities on the interface. Based on the comparison of the outcomes of both methods, it is suggested that in the process of improving usability of the contouring interface, the think aloud method can be applied to explore preferences of the user. The heuristic evaluation can be applied in designing the details of the interface.